A Revised Sound Energy Theory Based on a New Formula for the Reverberation Radius in Rooms with Non-Diffuse Sound Field - Higini ARAU-PUCHADES; Umberto BERARDI (Archives of Acoustics, 2014)
This paper discusses the concept of the reverberation radius, also known as critical distance, in rooms with non-uniformly distributed sound absorption. The reverberation radius is the distance from a sound source at which the direct sound level equals the reflected sound level. The currently used formulas to calculate the reverberation radius have been derived by the classic theories of Sabine or Eyring. However, these theories are only valid in perfectly diffused sound fields; thus, only when the energy density is constant throughout a room. Nevertheless, the generally used formulas for the reverberation radius have been used in any circumstance. Starting from theories for determining the reverberation time in non-diffuse sound fields, this paper firstly proposes a new formula to calculate the reverberation radius in rooms with non-uniformly distributed sound absorption. Then, a comparison between the classic formulas and the new one is performed in some rectangular rooms with non-uniformly distributed sound absorption. Finally, this paper introduces a new interpretation of the reverberation radius in non-diffuse sound fields. According to this interpretation, the time corresponding to the sound to travel a reverberation radius should be assumed as the lower limit of integration of the diffuse sound energy.